The Application of Discovery Learning Model with STEM Approach to Improve Critical Thinking Skills and Collaboration Skills of Students at Public Senior High School (SMA Negeri 3 Kupang) - I Wayan Sukarjita; Lidwina Felisima Tae (Postgraduate, University of Mataram, 2025)
This study aims to determine the application of Discovery Learning model with STEM approach in improving students' critical thinking skills and collaboration skills. This research is a pseudo-experiment with a research design of Randomized Control Group Pretest-Post-test which involved 2 experimental classes. The Discovery Learning model with STEM approach was applied in experimental class 1 while the Discovery Learning model without STEM approach was implemented in experimental class 2. By using t-test, it was found that there was a significant difference in positive critical thinking skills between students in experimental class 1 and 2, as evidenced by 3.042>1. 99346 respectively. Similarly, the critical thinking skills of students who used the Discovery Learning model with the STEM approach were also higher than students who were taught using the discovery learning model without STEM. Meanwhile, the results of students' collaborative skills when implementing the Discovery Learning model with STEM approach had an average percentage of 81% which could be grouped into very collaborative category. These results were higher than the class of Discovery Learning model without STEM approach, which accounted for 73% in collaborative category.